Multi-locus sequence typing of African swine fever viruses from endemic regions of Kenya and Eastern Uganda (2011–2013) reveals rapid B602L central variable region evolution - Onzere, Cynthia K.; Bastos, A.D.S.; Okoth, Edward A.; Lichoti, J.K.; Nyambego, Edwina B.; Owido, M.G.; Ndambuki, Gideon M.; Bronsvoort, B.M. de C.; Bishop, Richard P. (Springer, 2018)
The central variable region (CVR) within the B602L gene of the African swine fever virus (ASFV) is highly polymorphic within the 23 ASFV genotypes defined by sequencing of the C-terminal end of the p72 locus. Sequencing the p54 gene further discriminates ASFV genotypes that are conserved at the p72 locus. Variation in the thymidine kinase locus is a novel additional tool for ASFV genotyping whose application for this purpose is described for the first time herein. We evaluated genetic variation at these four polymorphic loci in 39 ASFV isolates obtained from outbreaks in Kenya and a region of Eastern Uganda between 2011 and 2013. Analysis of the p72 and p54 loci revealed high genetic conservation among these isolates; all clustered within p72 genotype IX and were similar to isolates associated with earlier outbreaks in East Africa. The thymidine kinase gene of the Kenyan isolates in this study were distinct relative to Southern African isolates and synonymous substitutions were observed among viruses from central Kenya. Analysis of the CVR within the B602L gene revealed two previously unknown polymorphisms that were restricted to Western Kenya and Eastern Uganda. A novel variant was revealed within CVR subgroup XXIV and a novel CVR subgroup XXIVa that contains tetrameric repeat F which has previously only been associated with p72 genotype I, was also identified for the first time in East Africa. Phylogeographic analysis of isolates based on CVR polymorphisms revealed rapid evolution and dissemination of variants present within ASFV genotype IX in East Africa.